Zur Entstehung der griechischen Chorlyrik - Lucarini, Carlo M. (Hyperboreus, 2019)
The aim of this paper is to show that the Greek choral lyric is not a direct descendant of the indo-European poetry. Whereas the language of poets like Pindar or Bacchylides is clearly strongly inﬂuenced by epic tradition, there is no means to show that substantial features of their poetry go back to the Indo-European stage. One of the most common metres used by choral poets are the dactylo-epitrites: basing myself on Berg’s theory about the origin of the hexameter, I show that the dactylo-epitrites derive their dactyls from the hexametric tradition. I also show that the Aeolic metres used by choral poets have a common origin with those used by Sappho and Alcaeus, but that the two traditions developed independently. A passage of Heraclides of Pontus shows that this scholar knew a tradition, according to which the oldest Greek poetry was hexametric. In my view, this assumption is to some extent right, as many metric forms (dactylo-epitrites, Archilochus’ asynarteta, anapests, elegy) derive from hexameter (attempts to show that extant inscriptions contain traces of pre-hexametric tradition are in my view misguided). Only aeolics and iambo-trochaics seem to be independent from the hexametric tradition.